Uji Aktivitas Antibakteri Ekstrak Daun Suruhan (Peperomia pellucida L. Kunth) terhadap Klebsiella pneumoniae - Destik Wulandari; Isna Jati Asih (Fakultas Farmasi Universitas Setia Budi, 2018)
Klebsiella pneumoniae is one of the pathogens which are gram negative bacteria andthat causes pneumonia. Treatment of Klebsiella pneumoniae bacterial infection is performedthrough the use of antibiotics. The phenomenon of resistance has encouraged the search fornatura-based antimicrobials where one of the plants with antibacterial potency is suruhan(Peperomia pellucida L. Kunth).The purpose of this study was to determine the antibacterial activity, the value of theMinimum Inhibitory Concentration (MIC) and the Minimum Killer Concentration (KBM) from theleaf extract of suruhan leaves on Klebsiella pneumoniae using a liquid dilution method. Theextraction method used in this study was maceration. The extract obtained tested with aconcentration of 100%; 50%; 25%; 12.5%; 6.25%; 3.125%; 1.562%; 0.781%; 0.391% and0.195% (v / v).The results showed that leaf extract had antibacterial activity against Klebsiellapneumoniae with a KBM value of 25%.